A mixed-methods approach to understanding water use and water infrastructure in a schistosomiasis-endemic community: case study of Asamama, Ghana - Kosinski, Karen Claire. (Tufts University. Tisch Library., 2016)
Background: Surface water contaminated with human waste may transmit urogenital schistosomiasis (UGS). Water related activities that allow skin exposure place people at risk, but public health practitioners know little about whysome communities with access to improved water infrastructure have substantial surface water contact withinfectious water bodies. Community-based mixed-methods research can provide critical information about water use and water infrastructure improvements. Methods: Our mixed-methods study assessed the context of water use in a rural community endemic for schistosomiasis.Results: Eighty-seven (35.2 %) households reported using river water but not borehole water; 26 (10.5 %) reportedusing borehole water but not river water; and 133 (53.8 %) households reported using both water sources. All households are within 1 km of borehole wells, but tested water quality was poor in most wells. Schistosomiasis is perceived by study households (89.3 %) to be a widespread problem in the community, but perceived schistosomiasis risk fails to deter households from river water usage. Hematuria prevalence among school children does not differ by household water use preference. Focus group data provides context for water preferences.Demand for improvements to water infrastructure was a persistent theme; however, roles and responsibilities with respect to addressing community water and health concerns are ill-defined.Conclusions: Collectively, our study illustrates how complex attitudes towards water resources can affect which methods will be appropriate to address schistosomiasis.